A Descriptive Study On Teaching Reading To The Eleventh Grade Students Of SMK Ganesha Tama Boyolali In 2012 / 2013 Academic Year - Handhika, Safitri; , Drs. Djoko Srijono, M. Hum; , Dra. Rini Fatmawati, M. Pd (2013)
This research is to describe teaching reading conducted by English teacher to the eleventh grade students of SMK Ganesha Tama Boyolali in 2012 / 2013 academic year. It is conducted to know the method used by English teacher and the process of teaching reading. The method that the writer applies is descriptive qualitative method. This does not include any calculation or statistic procedure. The methods of collecting data are interview, analyzing document and observation. The data are taken from syllabus, lesson plan, interview script, field note, and text book. The results of the research are: (1) the methods used in the teaching of narrative text in terms of reading skill to the eleventh grade students of SMK Ganesha Tama Boyolali in 2012/2013 academic year is Grammar Translation Method. (2) in teaching-learning process the teacher uses a fully-developed reading activity that supports students as readers through pre-reading, whilereading, post-reading.